Gestalt Theory and the Network of Traditional Hypotheses - Gilchrist Alan L. (Gestalt Theory, 2022)
Since at least the time of Helmholtz, the process of visual perception has been regarded as a two-stage affair consisting of an initial sensory stage corresponding to the proximal stimulus and a subsequent cognitive stage corresponding to the distal object. This construction amounts to an awkward mind body dualism wherein part of perception is done by the body and the other part is done by the mind. Gestalt theory rejected both raw sensations and their cognitive interpretation, offering a single unified perceptual process that responds to an extended pattern of stimulation. They proposed organizational rules that describe how objects arise from the indifferent retinal mosaic. The same grouping principles by which objects are segmented also function to segregate regions of uniform illumination. Lightness values can then be computed by comparing luminance values within each such framework of illumination, with no need for the mystical concept of taking the illumination into account.